"Perceived impact of music listening practices on task performance of clerical staff in service industry in Nigeria " (2016)
Music at The workplace is assumed to be a form of distraction to employees' performance. However, occupational stress and depression that affect 'workers productivity had been seen to have reduced at workplace through listening to music. It is against these diverse views that this research looked at the impact of listening to music on the task performance of clerical staff in the service industry. Purposively sampling technique was used to select 147 participants from the University and Federal Secretariat in Ibadan, Oyo State, Nigeria. Qualitative method was used for data collection and analysis. Finding showed that 96% of respondents listen to music while at work from music recorded on their laptops or from CDs played from their computers. About 74% did not see listening to music has been distractive to task performance rather it motivate them for better performance of tasks. About 94% (138) agreed that music at work smoothened their mood, help them to remain focused, and help in their being creative toward their job tasks. Finding showed that 30% of respondents want fast rhythm music be played to further 'soothing out their tension while carrying out their tasks and not only the current use of relaxed rhythm. Also, 85% of respondents supported regulating the volume of the music played so as not to serve as distraction to their task performance. Based on these findings, it was recommended that both rhythm and volume of music should be varied to take care of individual differences to enhance task performance.